Short Term Virologic Efficacies of Telbivudine versus Entecavir against Hepatitis B-Related Hepatocellular Carcinoma - Young Woon Kim; Jung Hyun Kwon; Eun Chung; Sung Won Lee; Jong-yul Lee; Jeong Won Jang; Kyu Won Chung; Soon Woo Nam (Gastroenterology Research and Practice)
Telbivudine has been reported to be more effective than lamivudine. However, because of the resistance rate to telbivudine (TLV), the current guidelines recommend entecavir (ETV) or tenofovir (TNV) as the first-line therapy for chronic hepatitis B. We investigated the short term virologic efficacy of TLV in comparison with ETV as the first-line agent of HBV suppression in HBV-related advanced HCC patients. A total of 86 consecutive patients with HBV-related HCC for whom antiviral treatment was initiated in Incheon St. Mary’s Hospital between 2010 and 2013 were analyzed. Virologic responses were investigated on the 4th, 12th, and 24th weeks of the antiviral therapies. In patients with advanced TNM stage cancer (stage 3 or 4) and poor liver function (Child-Pugh class B or C), the virologic response rates at weeks 12 and 24 were 25% (1/4) and 42.8% (3/7) in the TLV group and 33.3% (1/3) and 33.3% (1/3) in the ETV group, respectively (P=0.424, P=0.800). The short term efficacy of TLV was similar to that of ETV. Since TLV is highly cost-effective, it should be considered as a first-line antiviral agent in patients with advanced HCC, poor liver function, and short life expectancies.